2008
DOI: 10.2169/internalmedicine.47.1529
|View full text |Cite
|
Sign up to set email alerts
|

Sjoegren's Syndrome with Multiple Cystic Lesions and Pulmonary Arteriovenous Fistulae

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The etiology of the AVM could not be confirmed from histological findings. [ 14 ] Gupta et al also described the eccentric vessel location of multiple cysts in patients with SS although they could not find any AVM. [ 13 ] Our case is the second case of SS-associated pulmonary AVM reported globally and the first case of recurrence of pulmonary AVMs with aggravating multiple lung cysts in a patient with SS.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of the AVM could not be confirmed from histological findings. [ 14 ] Gupta et al also described the eccentric vessel location of multiple cysts in patients with SS although they could not find any AVM. [ 13 ] Our case is the second case of SS-associated pulmonary AVM reported globally and the first case of recurrence of pulmonary AVMs with aggravating multiple lung cysts in a patient with SS.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that Sjögren's syndrome could be associated with pulmonary arteriovenous fistula 6 and vaginoperineal fistula after perianal surgery 7 . However, no case of Sjögren's syndrome associated with the development of lacrimal fistula has been reported to date.…”
Section: Introductionmentioning
confidence: 99%